Endoscopic correction of primary vesicoureteric reflux: results in 94 ureters. Issue 6559 (29th November 1986) - O'Donnell, B; Puri, P
Abstract : Sixty one patients with primary vesicoureteric reflux were treated by endoscopic injection of Mentor Polytef paste. Seventy six of the 94 treated ureters showed complete disappearance of vesicoureteric reflux after one injection. Eight refluxing ureters required a second injection, one required a third, and one a fourth. Six ureters showed improvement in the grade of reflux after the first injection. Two ureters did not show any change in the grade of reflux after endoscopic injection. The amount of paste injected to correct reflux in the 94 ureters varied from 0.1 to 1.0 ml (mean 0.33 ml). Patients were followed up for three to 25 months (mean 13.4 months). Follow up micturating cystograms in the 94 ureters showed absence of reflux in 83. Eleven ureters showed recurrence of reflux. Recurrence of reflux was attributed to early technical difficulties and to insufficient amounts of polytef paste used in some cases. Follow up urograms did not show evidence of ureteric obstruction in the treated ureters. Endoscopic injection of polytef paste is a safe, simple, and effective procedure for primary vesicoureteric reflux and averts the need for open operation.